Community participation design for photovoltaic energy projects - Criollo Alvarez, Nancy Paulina; Maks-Davis, Michael; Rodríguez, Andrea (Estoa. Journal of the Faculty of Architecture and Urbanism, 2020)
This study took place in Llano Chico, a peri-urban parish in the Metropolitan District of Quito, in Ecuador. Photovoltaic energy was chosen, given the location of the site on the Equator with optimal solar conditions. The objective was to develop participatory methodology to determine the spatial configuration of a possible photovoltaic project. Community participation was key. Qualitative research methods were based on observation, snowball techniques, semi-structured interviews and a participatory workshop. The results open the doors to the possibility of having community photovoltaic energy for the installation of public lighting in informal residential areas that suffer from security issues. This could fill a void of services, due to public companies not being able to carry out operations in informal urban areas. The academic sector through strategies of community participation can bring about compelling opportunities that foster development.